Design and Implementation of A Solar-Driven Spy Security Motion Detector - Abiodun, Salami Sulaimon; Lasisi, Oyebamiji Hammed; Olasunkanmi, Oluwaseun Joel; Mujeeb, Babatunde; Tewogbade, Ayobami (Journal of Engineering and Scientific Research, 2025)
This project designs and implements a solar-powered spy security system with motion detection capability. The system integrates a solar panel, charge controller, battery, PIR sensor, 555 timer IC, buzzer, WiFi module, and a spy camera. The solar panel recharges the battery, providing a sustainable power source. The PIR sensor detects motion, triggering the 555 timer IC to activate the buzzer and spy camera. The system captures images or records videos only when motion is detected, conserving energy and memory space. The spy camera connects to a smart device via WiFi, enabling remote viewing of captured footage. Testing demonstrated the system's effectiveness as a reliable and efficient security solution. This project addresses the limitations of traditional CCTV cameras, providing a more efficient and sustainable solution for home security. The design leverages principles of electrical and electronics engineering, including circuit design, electronics, and control systems. Future enhancements can include integrating Artificial Intelligence to improve security and reduce false alarms.